An Attempt to Reduce the Background Free Radicals in Fingernails for Monitoring Accidental Hand Exposure of Medical Workers - Chryzel Angelica B. Gonzales; Jolan E. Taño; Hiroshi Yasuda (Applied Sciences, 2020)
While it is recognized that some medical workers could receive significantly higher radiation doses to their hands than the routinely monitored personal doses, accurate retrospective dosimetry of their hand exposure is still challenging. To solve this issue, a combination of electron spin resonance (ESR) measurement and fingernails is worth to be investigated. However, the application of fingernail ESR dosimetry requires establishing an effective protocol to eliminate the background signal (BKG) which changes due to mechanical stress and other unclear factors, so that the radiation doses would be precisely evaluated from the radiation-induced signals (RIS) only. Thus, the authors investigated possible applications of antioxidants to remove or reduce the BKG in fingernails. In the present study, the effectiveness of chemical treatment using the dithiothreitol (DTT) reducing reagent was examined in irradiated and unirradiated fingernails. Chemically and non-chemically treated fingernails were subsequently exposed to 20 Gy of 137Cs γ-rays and the time changes of the BKG and RIS were confirmed in two different storage conditions: vacuum chamber and freezer. The results show that the non-chemically treated fingernails displayed significant intra-individual variations in the peak-to-peak intensities of both BKG and RIS. RIS from chemically and non-chemically treated samples showed correlations after freezer storage; signals were more stable than the samples stored in the vacuum chamber. Moreover, while the BKG of non-chemically treated samples demonstrated higher levels than those chemically treated, the intra-individual variations were further reduced by the DTT treatment. Our results imply that the use of an antioxidant for hand washing of medical workers prior to starting their work could be effective in reducing the pre-existing free radicals in their fingernails. This also suggests a practical application of hand exposure monitoring using fingernails as a part of radiological emergency preparedness in occupations where radiation or radionuclides are used. Research for finding safer and easier-to-handle antioxidants is to be focused on in future studies.